2005
DOI: 10.1007/s10812-005-0139-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Human Serum Albumin According to the Data on the Phosphorescence Kinetics of a Luminescent Probe — Eosin

Abstract: The influence of the human serum albumin (HSA) denaturation by a surface-active substance (sodium dodecyl sulfate (SDS)) on the phosphorescence of a luminescent probe (eosin) has been investigated. The dependences of the eosin-phosphorescence intensity on the SDS concentration were determined at different pH levels of an HSA solution. It has been shown that at SDS concentrations lower than the critical concentration necessary for micelle formation, the hydrophobic interactions of eosin with the protein influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thirdly, it affects blood viscosity, which is extremely important for maintaining a normal blood pressure level. Fourthly, it serves as a carrier for hormones, lipids, mineral substances, and drugs.Various optical methods are used to detect structural conformational changes in protein molecules, such as laser correlation spectroscopy of dynamically scattered light [2-4], Raman spectroscopy [5], luminescent analysis methods [6][7][8][9]. In this work, to study the structure of HSA and the dynamics of its conformational rearrangements during denaturing when treated with SDS as a function of the solution pH, we used the luminescent spectral characteristics of the luminescent probe eosin in a buffered solution of the protein.…”
mentioning
confidence: 99%
“…Thirdly, it affects blood viscosity, which is extremely important for maintaining a normal blood pressure level. Fourthly, it serves as a carrier for hormones, lipids, mineral substances, and drugs.Various optical methods are used to detect structural conformational changes in protein molecules, such as laser correlation spectroscopy of dynamically scattered light [2-4], Raman spectroscopy [5], luminescent analysis methods [6][7][8][9]. In this work, to study the structure of HSA and the dynamics of its conformational rearrangements during denaturing when treated with SDS as a function of the solution pH, we used the luminescent spectral characteristics of the luminescent probe eosin in a buffered solution of the protein.…”
mentioning
confidence: 99%
“…In [25], it is shown that eosin also binds with bovine serum albumin. On the basis of spectral and kinetic studies [13], we found that almost all eosin is gathered at protein globules when HSA concentration in a water solution reaches HSA = 1 mg/mL. By changing the eosin concentration, it was obtained that the optimal concentration of eosin in HSA for the registration of prolonged luminescence is 4 ⋅ 10 −6 M.…”
Section: Resultsmentioning
confidence: 93%
“…This feature allows one to use the T-T energy transfer between donors and acceptors bound to a human serum albumin (HSA) to determine minor structural variations in proteins [12]. The phosphorescence of a probe, that is, an eosin bound to HSA macromolecules, turned to be sensitive to pH variations in protein solutions [13] and to the presence of heavy metal ions in proteins. Quenching of the eosin phosphorescence in the presence of heavy metal ions is used thus helping us determine the presence of heavy metals in human serum albumin [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrene bromide was photoexcited into the absorption band maximum. The lifetime of the pyrene bromide triplet state was determined using a specially developed pulsed spectrofluorimeter [19]. Three sections can be seen in the curve showing the dependence of the phosphorescence intensity on the solution photoirradiation time.…”
Section: Methodsmentioning
confidence: 99%